2012
DOI: 10.1017/cbo9781139005128
|View full text |Cite
|
Sign up to set email alerts
|

The Rationalization of Miracles

Abstract: During the Counter-Reformation in southern Europe, Catholic Church officials developed rules to legitimize miracles performed by candidates to sainthood. The Rationalization of Miracles uncovers a tacit understanding between central religious officials and local religious activists. Each group had a vested interest in declaring miracles: Catholic Church leaders sought legitimacy in the wake of the crisis of faith created by the Protestant Schism and religious acolytes needed Church approval to secure a flow of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 95 publications
0
7
0
1
Order By: Relevance
“…A final area that our participants identified as a source of institutional contradictions was the performance of miracles -broadly defined here as events that defy scientific explanation and that often consist of medically inexplicable healings (Parigi, 2012). Our interviewees emphasized that miracles were an integral part of their life as mystics:…”
Section: Performing Miraclesmentioning
confidence: 96%
See 1 more Smart Citation
“…A final area that our participants identified as a source of institutional contradictions was the performance of miracles -broadly defined here as events that defy scientific explanation and that often consist of medically inexplicable healings (Parigi, 2012). Our interviewees emphasized that miracles were an integral part of their life as mystics:…”
Section: Performing Miraclesmentioning
confidence: 96%
“…In this context, the experience of miracles was not only recurrent but, in certain cases, even predictably so (e.g., 'every first Friday of the month'). While our participants argued that miracles in their communities were ordinary occurrences performed by ordinary people, they were also aware that for mainstream Catholicism miracles were rare, exceptional events, and the exclusive domain of a limited set of highly gifted individuals (the saints), whose actions had to be thoroughly scrutinized before being included in the canon, or list, of recognized saints (Parigi, 2012). Cognizant of this institutional contradiction, community members distinguished their miracles as 'everyday prophets and healers' from the works of saints.…”
Section: Performing Miraclesmentioning
confidence: 99%
“…We ask how respondents understand the relationship between the Bible and evolution because the dominant thrust of the literature has shown that evolution is an area of contention among evangelicals and, to some extent, mainline Protestants (Berkman and Plutzer ; Binder ; Jelen and Lockett ; Plutzer and Berkman ). Further, we ask respondents about their understanding of miracles because the rise of science has provided competing interpretations for supernatural or magical events where previously religious institutions held a monopoly (Parigi ; Weber [1922] ) . While we did not ask respondents to explicitly compare miracles with science, our emphasis on believing miracles as described in the Bible asks respondents to reflect and question the supernatural events recorded in the Bible.…”
Section: Methodsmentioning
confidence: 99%
“…However, they also find that the density of monasteries in a city decreased the odds of reform, suggesting that a city's dependence on charitable institutions bolstered the Church. Pfaff and Corcoran also attempt to capture the influence of the contending Lutheran and Zwinglian wings of the early Protestant 10 In the wake of the Reformation, the Catholic Church responded to Protestant competition by canonizing more individuals and rationalizing the canonization process (see Barro and McCleary, 2016;Parigi 2012). 11 As we have noted, the Counter-Reformation did not take shape as a coherent strategy until after 1545.…”
Section: Iii3 Demand-side Channels Of the Reformationmentioning
confidence: 99%
“…Social networks should influence the diffusion of ideas and institutions through mechanisms such as information flows, the exercise of influence, and the capacity of groups to coordinate. Recent studies on the Reformation and its consequences are beginning to make explicit use of network concepts and methods (Kim and Pfaff 2012;Parigi 2012, Nexon 2009). Future research could do more to specify the concrete structural factors, agents of diffusion, and the relational structures underlying the rise, spread, and adoption of the Reformation.…”
Section: Taking Stock Of the New Empirical Reformation Literaturementioning
confidence: 99%